INFRARED DRYING AND EFFECTIVE MOISTURE DIFFUSIVITY OF APRICOT HALVES: INFLUENCE OF PRETREATMENT AND INFRARED POWER - Kayran, Seda; Doymaz, Ibrahim (WILEY, 2017)
The effect of pretreatment and infrared power on drying characteristics of apricot was investigated. The apricots were dried at 62, 74, 88 and 104 W infrared powers. It is observed that drying characteristics of apricot were greatly influenced by pre-treatment and infrared power. To select the most appropriate thin-layer drying model for drying process, ten mathematical drying models were fitted to the experimental data. Midilli et al. model satisfactorily described the drying kinetics of apricot. Effective moisture diffusivity (D-eff) ranged from 2.37x10(-9) to 6.23x10(-9) m(2)/s and calculated using the Fick's second law. The values of D-eff increased with the increase of infrared power. Activation energy was estimated by a modified Arrhenius type equation and found to be 1.63 and 1.67 kW/kg for control and SMB samples, respectively. Practical ApplicationsApricot is good source of health-promoting compounds such as vitamins, polyphenols, carotenoids and natural salicylic acids. Due to both their seasonal and perishable nature, apricots should be subjected to some form of preservation in order to make them available for later consumption. Drying is one of the most common methods used for apricot processing. Infrared drying has gained popularity as an alternative drying method for a variety of agricultural products. Compared with hot air drying, infrared radiation heating offers many advantages such as greater energy efficiency, heat transfer rate and heat flux, which results in reduced drying time and higher drying rate. The main objectives of this study were to investigate the effect of pretreatment and infrared power on the drying time, fit the experimental data to ten thin-layer drying models and compute effective moisture diffusivity of apricot halves.
Keywords: KINETICS; SLICES; RADIATION; DEHYDRATION; CARROT; DRYER; COLOR; HEAT; L.; Food Science & Technology